Parental Communication, Peer Role, and the Contextual Effect of School on Safe Sex Behavior among Adolescents in Mojokerto, East Java - Feny Lianawati; Argyo Demartoto; Rita Benya Adriani (Journal of Health Promotion and Behavior, 2018)
Background: